السلطة التنفيذية في النظام السياسي الإسلامي - Setiawan Bin Lahuri (Universitas Darussalam Gontor, 2017)
Since the death of the Prophet, Islam grew under a system of government known as khilâfah (caliphate) for 13 centuries until the frst World War happened. After that, the system ended by the Republic of Turkey which immediately erased the caliphate system applied by the Ottoman Empire, the last Islamic empire. In the Islamic history, the system of khilâfah has undergone several phases. It had begun in al-Khulafâ ‘al-Râsyidûn period. At that time, the leader of Muslims after the death of the Prophet was chosen through syûrâ system, which the chosen leader addressed as khalîfah approved by all Muslims. After al-Khulafâ al-Râsyidûn period passed, during the Umayyads, the Abbasids, to the Ottoman Turks, the Muslim leaders were no longer elected by syûrâ, but it turned to the monarchi system even though the regimes continued to adopt the khilâfah system. Nevertheless, the three khilâfah Islâmiyyah dynasties still maintain the principle of unity of the ummah. Therefore, the khilâfah Islâmiyyah run by the Umayyads, the Abbasids, and Ottoman Turks at that time made Islam the largest country in the world. This article tries to explain the Islamic system of government related to the executive institution called al-sulṭah al tanfîdhiyyah by referring to the best Islamic system of government in the period of al-Khulafâ ‘al-Râsyidûn. Although Islam implements the caliphate system, al sulṭah al-tanfîdhiyyah is also important because a khâlifah cannot handle the state with all its affairs alone.